Effect Of Foaming Properties Of Defatted Rice Bran On Rheological And Baking Properties Of Eggless Cake In Comparison With Egg White - Ahmad, A’inul Mardhiah (Universiti Sains Malaysia, 2020)
Defatted rice bran (DRB) can be produced by extracting its fat fraction which then can increase the shelf life and functional properties of the rice bran. This work aimed to evaluate the foaming property of DRB in comparison with egg white (EW) in eggless cake system. In preliminary study, rice bran was processed into three products such as stabilised rice bran (SRB), DRB, and rice bran protein concentrate (RPBC). These three rice bran products were then evaluated for its foaming properties and protein content before being selected to be incorporated in subsequent experiments. DRB showed superior foaming properties than SRB and RBPC even though its protein content is lower than RBPC. The cake batter and baked cake was formulated with DRB at varying concentration of 50% and 100% and were compared with control (100% EW). Cake batter formulated with 50% DRB produced batter with low density which related to its capability of retaining trapped air than in 100% DRB sample. The viscosity of the cake batter decreased with the increase in the level of DRB. The photomicrographs of cake batter with 50% DRB showed an increase in the number of gas bubbles and more uniform size distribution which comparable with the control indicating low batter density. Meanwhile, the increasing incorporation of DRB in the formulation had produced cake with lower volume, higher density and lower lightness value compared to the control. However, cake formulated with 50% DRB produced cake with smaller bubble size and higher number of gas bubbles per section of the cake than control and 100% DRB sample. This result contributes to the high quality of cake texture especially in texture parameter such as chewiness, cohesiveness, and resilience.